Psychosocial Challenges Facing Young People With Inherited Metabolic Disorders and Their Parents: A Systematic Review - Clara Sherlock; Kim Clarke; Norah Jordan (JIMD Reports)
ABSTRACT Recent advancements in new‐born screening have reduced the risk of life‐threatening complications associated with inherited metabolic disorders. However, the risk of negative psychosocial effects on families persists. The aim of the present study was to systematically review the literature concerning the psychosocial challenges experienced by young people with metabolic conditions and their families, to inform the development of supports that meet the needs of those linked with metabolic services. The electronic databases MEDLINE, CINAHL, PsychInfo, and Psychology and Behavioural Sciences Collection were searched for studies examining psychosocial challenges reported by families with inherited metabolic conditions, over the last two decades. Five‐thousand sixty‐seven articles were screened for relevance. Twenty‐nine studies met the inclusion criteria. Study quality and reliability were independently assessed by two reviewers. Results highlighted the myriad of physical, social, psychological and practical challenges experienced by young people with metabolic conditions and their families. These challenges included social isolation, burden of care, and learning and emotional difficulties. Findings reiterate the importance of developing peer support groups and delivering psychoeducation to families, as well as the central role psychology and social work should play in metabolic MDTs, to improve families' experiences and outcomes.